Inovasi Gerakan Sedekah Bibit Cabai dan Pemanfaatan Pekarangan menuju Ketahanan Pangan Berkelanjutan di Kabupaten dan Kota se-Indonesia - Hikmah, Nur 'Izzatul (Faculty of Social Science, Universitas Negeri Semarang, 2019)
Chili was a staple in Indonesia every year since Eid Mubarok and until the end of the year continuously experience price increases. Chili prices were continuously creeping up, causing the holding of the movement to use new seeds of chili to be planted. The use of home yard to be a solution for people who lack land to plant chili. The purpose of this research was to know the movements that have existed in major cities in Indonesia related to the alms of chili seedlings and the utilization of yard to towards food security, especially the resilience of chili commodities. The research method, conducted with literature study and document studies (secondary data) that could be good from the source in the form of books, reports, or news from mass media print or online. The result of the research shows that there are 3 chili algae movements in Indonesia namely the National Movement of Planting 10 million Chili Trees in Cilodong West Java, the Nandur Movement and One Million Seeds and the Chili Seeds in Surabaya, and the Beautiful and Comfortable Pure Land Movement (PKK) in Bogor and the utilization of home yard for food security can maintain chili commodity.